Model pengembangan kurikulum siswa cerdas istimewa mata pelajaran bahasa Indonesia - Sujinah, Sujinah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Without the provision of differentiated services for gifted students, a program would merely label them as gifted students without offering a truly gifted program. The potential risk that may arise when gifted students receive regular instructional services is underachievement; therefore, it is necessary to implement a differentiated curriculum model for gifted students. This article describes not only the curriculum model used in schools with gifted student programs or acceleration classes, but also examines the model’s validity, practicality, and effectiveness. The method employed was a combined model of RDR (research, development, research) and R2D2 (recursive, reflective, design, and development), incorporating adaptations, modifications, and/or specific transformations. Data were collected through documentation, unstructured interviews, questionnaires, and observation. The curriculum was developed based on the following procedures: Minister of National Education Regulation (Permendiknas) No. 22 of 2006, identification, escalation, determination of essence, mapping, organization, and time allocation.